Farmer business school: Product catalogue - International Potato Center; Smallholder Livelihood Development Project (International Potato Center, 2018)
Farmer Business School (FBS) is a participatory action learning process that involves farmer groups’ participation in agricultural value chains. As part of capacity strengthening, FBS comprises a series of group-based experiential learning activities over a production marketing cycle while interacting with other chain actors and stakeholders.